2017
DOI: 10.1159/000479900
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of the Chemical Composition and In Vitro Cytotoxic Mechanisms of Pallines Spinosa Flower and Leaf Essential Oils Against Breast Cancer Cells

Abstract: Background/Aims: In our quest for new natural anticancer agents, we studied the cytotoxicity of the essential oils extracted from flowers and leaves of Pallines spinosa. Methods: The essential oils were extracted by hydrodistillation and solid phase microextraction (SPME) from flowers and leaves of the plant and their composition was determined by GC/GC-MS. The cytotoxicity of the oils was evaluated against MCF-7 and MDA-MB-231 breast adenocarcinomas, and the non-cancerous MCF-10-2A cells, using a flow cytomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…The L-PSEO was composed of 51.60% of oxygenated STs and 34.06% of SQ hydrocarbons. F-PSEO had stronger anticancer results for MCF7 and MDA-MB-231 and both EOs induced a caspase-dependent and caspase-independent apoptosis and altered the levels of Bcl-2 and Bax proteins [46].…”
Section: Antitumoral Activity Of Eos and Bioactive Compoundsmentioning
confidence: 93%
“…The L-PSEO was composed of 51.60% of oxygenated STs and 34.06% of SQ hydrocarbons. F-PSEO had stronger anticancer results for MCF7 and MDA-MB-231 and both EOs induced a caspase-dependent and caspase-independent apoptosis and altered the levels of Bcl-2 and Bax proteins [46].…”
Section: Antitumoral Activity Of Eos and Bioactive Compoundsmentioning
confidence: 93%
“…Thus, the ethanolic FE of Thevetia peruviana stimulated apoptosis of cervical cancer HeLa cells triggered by TNFα or TRAIL, two ligands of death receptors, by activating caspase-3 and PARP. Notably, FE of T. peruviana diminished the expression of the anti-apoptotic protein survivin (Managit, Sakurai, and Saiki, 2017) A FE containing essential oils of Pallines spinosa decreased cell viability of breast cancer cells while a minor effect was detected in immortalized mammary epithelial cells (Saleh et al, 2017). This effect was accompanied by a decrease of the anti-apoptotic protein Bcl-2 and an increase of the pro-apoptotic protein Bax Flowers from Antirrhium majus are among the most popular edible flowers, frequently used from preparing foods and drinks.…”
Section: Extracts From Flowers With Anticancer Effectmentioning
confidence: 97%
“…Plants essential oils can be used as alternative sources of Ae. aegypti larval control agents (Aguiar et al 2010, Gois et al 2011, Dias & Moraes 2014, Pavela 2015, Carvalho et al 2016, De Sousa et al 2016, Mendes et al 2017, Nascimento et al 2017, Mar et al 2018, and have been reported to show cytotoxic activity when tested on human cancer cell lines (Gautam et al 2014, Lesgards et al 2014, De Sousa et al 2016, Kumar et al 2016, Saleh et al 2017, Tavakoli et al 2017, Vasilijevic et al 2018.…”
Section: Introductionmentioning
confidence: 99%